Income Analysis to Increasing Business Profits at MSMEs Teh Tarik Annura Salatiga - Tiwi Umaydatul Febianty Sukma; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Westscience Press, 2024)
Teh Tarik is a drink that is spread across Southeast Asian countries from Malaysia, Singapore and Indonesia. Teh Tarik Annura was founded in 2019. The aim of this research is to analyze revenue in increasing business profits received by MSME Teh Tarik Annura. In this research, quantitative descriptive methods were used, namely case studies that used observation, interviews, documentation and literature study methods. From the data that has been calculated, business income and profit during the period in 2023 experienced increases and decreases every month with an average income of IDR. 23,250,000 starting from January to December 2023, and with an average operating profit of Rp. 17,188,750 from January to December 2023. Data shows that in one period in 2023, from the data that has been calculated, revenue and operating profit increased four times, in March-April there was an increase in income of 29%, in May-June experienced an increase of 14%, in August-September there was an increase of 20%, and in November-December there was an increase in revenue of 19%. Operating profits also experienced an increase. March-April experienced an increase in operating profits of 40%, in May-June there was an increase of 46%, in August-September there was an increase of 20%, and in November-December there was an increase in income of 16%. The results of the research show that if income increases, the operating profit received will increase, and if expenses increase but income is greater, then operating profit will not decrease significantly.